2011
DOI: 10.1159/000333279
|View full text |Cite
|
Sign up to set email alerts
|

Complete Response of Advanced Hepatocellular Carcinoma with Multiple Lung Metastases Treated with Sorafenib: A Case Report

Abstract: Sorafenib, an oral multikinase inhibitor, has demonstrated clinical efficacy in patients with advanced hepatocellular carcinoma (HCC). However, in the SHARP trial (Sorafenib HCC Assessment Randomized Protocol trial) and the Asia-Pacific trial (conducted in the Asia-Pacific region), no cases of complete response (CR) were reported. Thereafter, only a relatively small number of CR cases were reported worldwide for sorafenib therapy. We herein report a case of CR in a patient treated with sorafenib for 4 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 26 publications
1
39
1
Order By: Relevance
“…Abbadessa et al (28) reported that HCC patients benefited from the long-lasting effects of sorafenib. In addition, we have previously treated a patient with advanced HCC with lung metastasis who achieved CR with sorafenib (29). These results suggest that a number of patients may achieve an objective response with sorafenib therapy (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Abbadessa et al (28) reported that HCC patients benefited from the long-lasting effects of sorafenib. In addition, we have previously treated a patient with advanced HCC with lung metastasis who achieved CR with sorafenib (29). These results suggest that a number of patients may achieve an objective response with sorafenib therapy (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 85%
“…In addition, we have previously treated a patient with advanced HCC with lung metastasis who achieved CR with sorafenib (29). These results suggest that a number of patients may achieve an objective response with sorafenib therapy (27)(28)(29)(30). However, characteristics of the patients benefiting from, as well as features associated with sorafenib-resistance have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib therapy did not achieve a complete response in 299 patients in the Sorafenib Hepatocellular Carcinoma Assessment Randomized Protocol (SHARP) study or 150 patients in the Asian Pacific study; the partial response rates were 2.0% and 3.3%, respectively (6,7). Only a few studies have reported a complete response in HCC patients receiving sorafenib treatment (8)(9)(10)(11)(12)(13)(14)(15)(16). We listed these in order of the time to cessation (Table).…”
Section: Discussionmentioning
confidence: 99%
“…The current clinical practice guideline of the Barcelona Clinic Liver Cancer staging system4 recommends sorafenib as standard treatment for advanced HCC. The achievement of a CR after sorafenib treatment has rarely been reported,516 and the reduction of doses because of adverse effects is frequent 7,9,15. Our study reports that a patient with advanced HCC with right portal vein thrombosis (PVT) was treated with sorafenib.…”
Section: Introductionmentioning
confidence: 93%